Venous Thromboembolism Prediction in Postoperative Urogynecology Patients: The Utility of Risk Assessment Tools. Issue 8 (August 2020) - Heft, Jessica; Goulder, Alison; Schneiter, Mali; Adam, Rony
Abstract : Objectives: The aim of the study was to evaluate the utility of risk assessment tools (Rogers and Caprini Score models) in predicting venous thromboembolism (VTE) in a urogynecology patient population. Methods: All surgical patients underwent a procedure in the operating room with 1 of 7 female pelvic medicine and reconstructive surgery. Attendings from January 1 to December 31, 2015, were investigated. Rogers and Caprini Scores were calculated for each patient as well as the occurrence of any VTE in the 30 days after surgery. Patients were then grouped into risk categories based on the American College of Chest Physicians guidelines. Results: A total of 783 patients were identified and included in this study. The average patient age was 58 years (range = 18–89 years). The average operative time was 109 minutes (range = 4–491 minutes). Most patients obtained a Rogers Score of 5 (32%) and a Caprini Score of 4 (34%). Based on Caprini scoring, the American College of Chest Physicians category distribution was as follows: 10% low risk, 61% moderate risk, and 29% high risk. Based on Rogers scoring, this distribution was as follows: 96.8% very low risk, 3.1% low risk, and 0.1% moderate risk. Two VTE events were identified in the cohort. Overall, the incidence of VTE was 0.26%. Conclusions: The standard VTE risk assessment tools grade urogynecology patients very differently. Although the Caprini Scale seems to appropriately differentiate individual patient VTE risk, the Rogers Scale does not adequately stratify this risk, thus potentially limiting its use within this population.